PEMANFAATAN LIMBAH FURNITURE(PLYWOOD DAN HPL) SEBAGAI BAHAN PRODUK TURUNAN DI TRUSTIC INTERIOR - Eddi Indro Asmoro; Prana Sutta Widagdo (Jurnal Ilmiah Dinamika Teknik, 2021)
Today, the use of wood raw materials is starting to increase dramatically, making wood supplies begin to decrease. To overcome this problem, an artificial board was made in the form of MDF (medium density fiberboard), blockboard, particleboard, and plywood (multiplex). The problem of waste in the furniture industry generally disrupts the space in the production space and the effort that is currently being made is simply by selling the waste directly. Trustic Interior initiated the use of furniture waste as raw material for derivative products, where the raw materials used were waste of plywood and High Pressure Laminate (HPL). The utilization of furniture waste made from plywood and HPL as raw material in Trustic Interior is done by classifying it in various categories of shapes and sizes in the form of dimensions of thickness, width and length. Waste that has almost the same dimensions is grouped together. Then the raw materials are processed into various derivative products such as fung- cube, children's puzzles, skateboards, and other creative toys. One of the derivative products in interior design from waste of plywood and HPL as raw materials is end table. End Table is one of the derivative products that uses small plywood and HPL waste with dimensions of 450 x 450 x 610 mm. With added value as a derivative product made from waste raw material, the end table generates revenues of Rp. 8.352,000 (3 products) - Rp. 12,840,000 (5 products).